2019
DOI: 10.1002/wer.1178
|View full text |Cite
|
Sign up to set email alerts
|

Mine drainage: Treatment technologies and rare earth elements

Abstract: The recent research and development on mine drainage published in 2018 was summarized in this annual review. In particular, this review was focused on two main aspects of mine drainage: (a) advances in treatment technologies and (b) rare earth elements in mine drainage and its recovery. The first section covers passive treatment technologies and active treatment options, including physiochemical treatment and biological treatment. The second section includes the characterization of rare earth elements in mine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 77 publications
0
11
0
Order By: Relevance
“…Due to the much higher economic values of REEs relative to the major metals such as iron and aluminum present in AMD, several studies regarding REE recovery from AMD have been reported recently [9,10,12,22,124,[141][142][143][144]. In one of our prior studies [10], staged precipitation tests were performed on a coal mine drainage (6.14 ppm of REEs), and a REE pre-concentrate containing 1.1% of REEs was produced in the pH range of 4.85-6.11.…”
Section: Ree Recovery From Acid Mine Drainagementioning
confidence: 99%
“…Due to the much higher economic values of REEs relative to the major metals such as iron and aluminum present in AMD, several studies regarding REE recovery from AMD have been reported recently [9,10,12,22,124,[141][142][143][144]. In one of our prior studies [10], staged precipitation tests were performed on a coal mine drainage (6.14 ppm of REEs), and a REE pre-concentrate containing 1.1% of REEs was produced in the pH range of 4.85-6.11.…”
Section: Ree Recovery From Acid Mine Drainagementioning
confidence: 99%
“…Due to the much higher economic values of REEs relative to the major metals such as iron and aluminum present in AMD, several studies regarding REE recovery from AMD have been reported recently [9,10,12,22,124,[141][142][143][144]. In one of our prior studies [10], staged precipitation tests were performed on a coal mine drainage (6.14 ppm of REEs), and a REE pre-concentrate containing 1.1% of REEs was produced in the pH range of 4.85-6.11.…”
Section: Ree Recovery From Acid Mine Drainagementioning
confidence: 99%
“…For instance, elevated As levels in high-alkalinity drainage have been mostly attributed to the oxidation of arsenopyrite or As-bearing pyrite that had been neutralized [137,138] but may also originate from natively As-rich carbonate phases in the absence of Fe-oxides [128]. With the increased interest in the development of rare earth element (REE) mines, there is an increasing interest in REE geochemistry and ecotoxicity [139][140][141]. REE-bearing minerals can be found in many different geological settings (although not necessarily at economic concentrations), and REEs can be found as trace contaminants in other minerals.…”
Section: The Geochemistry Of Neutral Drainagementioning
confidence: 99%